Moran’s Index Spatial Analysis On The New Case Detection Rate of Leprosy in West Java 2022 - Meuthia Jasmine; Arief Wibowo (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Leprosy is a chronic infectious disease, neglected tropical disease caused by Mycobacterium leprae. Leprosy is divided into two types based on the number of lesions on the skin. If there are less than 5 lesions, leprosy is classified as paucibacillary (PB) and if there are more than 5 lesions, leprosy is classified as multibacillary (MB). Indonesia is ranked third in the world after Brazil with 762 new cases of grade 2 disability leprosy by 2022. Therefore, spatial analysis of the new case detection rate of leprosy in West Java 2022 is needed. Objective: To determine wheter there are spatial dependency with the new case detection rate of leprosy in West Java 2022 Method: Quantitative research that utilises secondary data by conducting spatial analysis on the new case detection rate of leprosy in West Java 2022 using Moran's Index and LISA tests. Result: There are 5 areas namely Bekasi, Karawang, Subang, Indramayu, and Cirebon that have not yet reached the national target in eliminating leprosy. The value of Moran's I = 0.241 and p-value 0.0090 < ? (0.05) which means that there is a weak positive spatial dependence on the number of new leprosy cases in West Java Province 2022. There is 1 region that is in the high-high quadrant, namely Cirebon and there are 4 regions in the low-low quadrant, namely Cimahi City, Bandung City, Garut, and Tasikmalaya. Conclusion: A small number of areas in West Java Province still have not reached the national target of eliminating leprosy, which is a CDR of <5 per 100.000 population, namely Bekasi, Karawang, Subang, Indramayu, and Cirebon. There are 5 areas that have spatial linkages in the new case detection rate of leprosy in West Java Province in 2022 based on the significance value. The region in the high-high quadrant is Cirebon and there are 4 regions in the low-low quadrant, namely Cimahi City, Bandung City, Garut District, and Tasikmalaya District.